2021
DOI: 10.1101/2021.09.28.461955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of Inefficient BCI Users based on Cognitive Skills and Personality Traits

Abstract: BCI inefficiency is one of the major challenges of motor imagery brain-computer interfaces (MI-BCI). Past research suggests that certain cognitive skills and personality traits correlate with MI-BCI real-time performance. Other studies have examined sensorimotor rhythm changes (also known as mu suppression) as a valuable indicator of successful execution of the MI task. This research aims to combine these insights by investigating whether cognitive factors and personality traits can make predictions of a users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In this case, both past and current research suggest a strong correlation between the user's self-reported operation performance and their self-reported performance satisfaction with their BCI performance (see for a discussion Kübler et al, 2015). In addition, the user's self-reported and perceived effectiveness (Kübler et al, 2014) and their acceptability of the BCIs as well as their affinity with technology (e.g., Hagedorn et al, 2021;Leeuwis et al, 2021) seem to modulate BCI performance among different vulnerable end-user groups. This may include patients with stroke or with mental health conditions (e.g., Al-Taleb et al, 2019;Voinea et al, 2019).…”
Section: User Traits and Bci Performance: The Role Of Personality Traitsmentioning
confidence: 81%
“…In this case, both past and current research suggest a strong correlation between the user's self-reported operation performance and their self-reported performance satisfaction with their BCI performance (see for a discussion Kübler et al, 2015). In addition, the user's self-reported and perceived effectiveness (Kübler et al, 2014) and their acceptability of the BCIs as well as their affinity with technology (e.g., Hagedorn et al, 2021;Leeuwis et al, 2021) seem to modulate BCI performance among different vulnerable end-user groups. This may include patients with stroke or with mental health conditions (e.g., Al-Taleb et al, 2019;Voinea et al, 2019).…”
Section: User Traits and Bci Performance: The Role Of Personality Traitsmentioning
confidence: 81%
“…Traditionally, MI-BCIs operate on machine learning (ML) algorithms in which spatial features associated with movement imagination are recognized. The imagining of a left or right body movement is accompanied by a lateralization of event-related (de)synchronization (ERD/ERS) in the mu (7-13 Hz) and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) frequency bands of EEG signals [7][8][9][10]. This brain activity feature is usually picked up by the Common Spatial Pattern (CSP) algorithm [11] and serves as an input to the ML algorithm classifying the imagined body movements.…”
Section: Introductionmentioning
confidence: 99%
“…This is called 'BCI illiteracy' [12] or 'BCI inefficiency' [13], where a user is considered unable to control a BCI, even after extensive training. While multiple studies have focused on identifying the inefficient users early on in research or adapting the BCI training to them [e.g., [14][15][16], the issue of BCI inefficiency might be argued more nuanced; as successful BCI control depends on a synergy between man and machine, and therefore enhancements on both sides are needed to reach efficient control [13].…”
Section: Introductionmentioning
confidence: 99%